2021
DOI: 10.1186/s13045-021-01081-7
|View full text |Cite|
|
Sign up to set email alerts
|

HLA-A2.1-restricted ECM1-derived epitope LA through DC cross-activation priming CD8+ T and NK cells: a novel therapeutic tumour vaccine

Abstract: Background CD8+ T cell-mediated adaptive cellular immunity and natural killer (NK) cell-mediated innate immunity both play important roles in tumour immunity. This study aimed to develop therapeutic tumour vaccines based on double-activation of CD8+ T and NK cells. Methods The immune Epitope database, Molecular Operating Environment software, and enzyme-linked immunosorbent assay were used for epitope identification. Flow cytometry, confocal micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…High dosages of CTX reduce the number of dendritic cells (DCs) and alter the polarization of Th cells, inducing immunosuppression [ 31 ]. The DCs of CD8 + T and CD56 + NK cells are activated, enhancing the cross-activation of adaptive and innate immune responses [ 32 ]. Polysaccharides from Pleurotus eryngii with a branch of β-1,6-glucan increase the proportion of CD4 T and CD8 T cells to improve immunity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…High dosages of CTX reduce the number of dendritic cells (DCs) and alter the polarization of Th cells, inducing immunosuppression [ 31 ]. The DCs of CD8 + T and CD56 + NK cells are activated, enhancing the cross-activation of adaptive and innate immune responses [ 32 ]. Polysaccharides from Pleurotus eryngii with a branch of β-1,6-glucan increase the proportion of CD4 T and CD8 T cells to improve immunity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NK cells are essential for T cells to mediate tumor immunity. Studies have found that the clearance of NK cells also caused a reduction in the recruitment and activation of tumor specific CD8+T cells ( André et al, 2018 ; Yu et al, 2021 ). Sta Maria et al reported ( Sta Maria et al, 2015 ), in the xenograft tumor of human colorectal adenocarcinoma mice, compared with the group that did not receive ldbFUS treatment, the group that injected MBs + NK cells into the tail vein of mice and underwent ultrasound irradiation had significantly more NK cell aggregation.…”
Section: Mechanism and Application Of Ultrasound Combined With Microb...mentioning
confidence: 99%
“…iNKT cells are CD1d-restricted, lipid-reactive T cells with predominantly immunomodulatory properties to produce cytokines and chemokines and modulate other immune cells ( 84 ). Additionally, iNKT cells can provide cytotoxic immune responses via cytotoxic granules and death receptor pathways ( 85 ). In arthritis, some iNKT are promoted while others are suppressed.…”
Section: Invariant Natural Killer T (Inkt) Cellsmentioning
confidence: 99%